Diet quality and nutrient density in pregnant women according to adherence to Mediterranean diet - Castro-Barquero, Sara; Larroya, Marta; Crispi, Fátima; Estruch, Ramon; Nakaki, Ayako; Paules, Cristina; Ruiz-León, Ana María; Sacanella, Emilio; Freitas, Tania; Youssef, Lina; Benitez, Leticia; Casas, Irene; et al. (Frontiers in Public Health, 2023)
Background & Aims: The dietary pattern followed during pregnancy, specifically healthy dietary patterns such as the Mediterranean diet, is a key factor in the mother’s and the offspring’s health. Pregnant women dietary intake is not enough to cover the micronutrient requirements of pregnancy, and higher adherence to the Mediterranean diet may improve dietary quality and nutritional density. The aim of the present study was to describe the dietary nutrient intake and diet quality during pregnancy and to evaluate whether a high adherence to Mediterranean diet was associated with a more adequate intake of micronutrients. Methods: This was a cross-sectional study with 1,356 pregnant women selected during the routine second trimester ultrasound scan (19-23 weeks’ gestation). Energy and nutrient intake were calculated using a validated 151-item semi-quantitative food frequency questionnaire and nutrient density was estimated dividing the absolute nutrient intake by total energy intake. Adherence to the the Mediterranean diet was evaluated with a 17-item Mediterranean diet adherence score. The criterion used for risk of inadequate nutrient intake has been set below two thirds (2/3) of the dietary reference intakes. The differences were assessed by multivariate linear regression models adjusted for confounders. Results: A significant proportion of pregnant women had an inadequate intake of macro and micronutrient that was lower in those with high adherence to the Mediterranean diet (≥12 points, n=122, 19%), including calcium (the Mediterranean diet high adherence 2.5% vs. low adherence 26.7%, p<0.001), magnesium (0% vs. 7.6%, p=0.001), iron (24.5% vs. 74.1%, p<0.001), and vitamin B9 (0% vs. 29.8%, p<0.001), vitamin C (0% vs. 1.9%, p=0.033), and vitamin D (61.5% vs. 92.8%, p<0.001) intake. High adherence to Mediterranean diet was associated with higher intake of protein, monounsaturated fatty acids, fiber, vitamins (B1, B9, C, D), calcium, magnesium, iron, zinc, phosphor, potassium, essential fatty acids, and α-linolenic acid. Conclusion: High adherence to Mediterranean diet was associated with higher diet quality and lower proportion of inadequate micro and macronutrient intake. The Mediterranean diet promotion, particularly among pregnant women, may be a useful and public health strategy to avoid overweight and nutrient deficiencies.